Analiticidade, na variável espacial, da solução do problema de Caucky para a equação de KdV - Miotto, Márcio Luís (2006)
In this work we use bilinear estimates and point fix theorem to show that the solution to the initial value problem for the Korteweg-de Vries equation with analytic periodic initial data is analytic and periodic in the space variable.